Pathogenetic significance of transforming growth factor β1 in patients with colorectal cancer - A. V. Chetveryakov; V. L. Tsepelev (Фундаментальная и клиническая медицина)
Aim. We aimed to evaluate levels of transforming growth factor β1 (TGF-β1) in the serum, lymph nodes, and primary tumour in patients with colorectal cancer.Materials and Methods. Here we enrolled 44 patients with colorectal cancer and 25 patients with benign tumours of the colon admitted to Chita Regional Cancer Centre in 2019-2020. The control group included 25 patients with colon injury. The concentration of TGF-β1 in the serum, lymph nodes, and tumour homogenate was measured by flow cytometry (CytoFlex LX analyzer and LEGENDplex HU multiplex analysis kit).Results. Serum level of TGF-β1 in patients with colorectal cancer was 1.58-fold lower than in those with benign colon tumours and 1.38-fold lower than in the control group. In contrast, TGF-β1 level in tumor tissue was 5.91 (3.86; 7.81) fold higher than in the injured colonic tissue from the control group, although there were no statistically significant differences between the cancerous tissue and benign neoplasms.Conclusion. TGF-β1 is increased in tumour tissue but reduced in the serum of patients with colorectal cancer.